Effects of excitatory transcranial magnetic stimulation over the different cerebral hemispheres dorsolateral prefrontal cortex for post-stroke cognitive impairment: a systematic review and meta-analysis - Han, Kaiyue; Liu, Jiajie; Tang, Zhiqing; Su, Wenlong; Liu, Ying; Lu, Haitao; Zhang, Hao (Frontiers in Neuroscience, 2023)
Background: Post-stroke cognitive impairment (PSCI) is a significant health concern. Transcranial magnetic stimulation (TMS) is considered a promising rehabilitation therapy for improving cognition, and the effects of excitatory TMS on PSCI have received much attention in recent years. However, the effects of different cerebral hemispheres on excitatory TMS treatment of cognitive impairment have not been studied. This review aimed to study the effects of excitatory TMS over the dorsolateral prefrontal cortex (DLPFC) of different cerebral hemispheres on the cognitive function of patients with PSCI. Methods: Literature published in PubMed, Web of Science, Embase, Cochrane Library, Scopus, and Wiley from inception to September 30, 2022, were searched. Two researchers independently performed literature screening, data extraction, and quality assessment. Furthermore, we conducted a meta-analysis using RevMan software (version 5.4) and rated the strength of evidence using GRADEpro. Results: A total of 19 studies were included in this meta-analysis. The results showed that excitatory TMS over the left hemisphere DLPFC was significantly better in improving global cognition, memory, attention, executive, P300 latency, and depression (SMD = 0.95, 95% CI 0.26-1.63, P = 0.007) than that of the control group, but the effect on improving activities of daily living (ADL) was unclear (P = 0.03 vs. P = 0.17). Subgroup analysis further showed that excitatory TMS over the right hemisphere DLPFC was effective in improving the global cognition of PSCI patients (P < 0.00001), but the stimulation effect over the ipsilateral hemisphere DLPFC was unclear (P = 0.11 vs. P = 0.003). Additionally, excitatory TMS over the ipsilateral hemisphere DLPFC showed no statistical difference in improving ADL between the two groups (P = 0.25). Conclusions: Compared to other hemispheric sides, excitatory TMS over the left hemisphere DLPFC was a more effective stimulation area, which can significantly improve the global cognitive function, memory, attention, executive, P300 latency, and depression in patients with PSCI. There was no apparent therapeutic effect on improving activities of daily living (ADL). In the future, more randomized controlled trials with large-sample, high quality, and follow-up are necessary to explore a usable protocol further.